Adaptive Torque-based Vehicle Slip Control using Super-twisting Theorem for Steering Vehicle Control on Cornering Road - N. M., Adam; A., Irawan (2021)
The inertia of vehicle's slip caused by oversteered is a crucial part that need to be considered in vehicle dynamics and control system design especially in the cornering road. This is particularly important for steering vehicles, as inertia might lead to high accidents with peer walls. Therefore, this research has taken the initiative to contribute to the investigation of a better solution for vehicle control challenges that are special to cornering road maneuvering. The adaptive torque-based vehicle slip control (AT-VSC) is proposed using super-twisting algorithm to allow coping with the issue by indirectly shaping inertia forces. The Rack Steering Vehicle (RSV) is used in this research as the targeted platform. The vehicle velocity, inertia, and kinetic energy reduction of the RSV in the cornering track were all simulated and analyzed. The results shows that the proposed control strategy AT-VSC offers improved performance in terms of speed increase time and vehicle stability that gives impact to the RSV being skidded or collided to any obstacles during cornering period.